2015
DOI: 10.1161/jaha.115.002435
|View full text |Cite
|
Sign up to set email alerts
|

Heart Retransplant Recipients Have Better Survival With Concurrent Kidney Transplant Than With Heart Retransplant Alone

Abstract: BackgroundHeart retransplant (HRT) recipients represent a growing number of transplant patients. The impact of concurrent kidney transplants (KTs) in this population has not been well studied. We tested the hypothesis that recipients of HRT with concurrent KT (HRT‐KT) would have worse survival than recipients of HRT alone.Methods and ResultsA retrospective analysis of the United Network of Organ Sharing database was performed for all patients undergoing HRT from 1987 to 2011. There were 1660 HRT patients, of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 49 publications
(86 reference statements)
0
8
0
Order By: Relevance
“…Adult studies have shown that HRTx recipients have better survival with combined KTx than with HRTx alone. 31 Thus combined heart-kidney transplant could be considered in these patients with allograft failure and ESRD. Future work may encompass identifying threshold eGFR that validates combined heart-kidney transplant in this high risk population before the progression to ESRD.…”
Section: Discussionmentioning
confidence: 99%
“…Adult studies have shown that HRTx recipients have better survival with combined KTx than with HRTx alone. 31 Thus combined heart-kidney transplant could be considered in these patients with allograft failure and ESRD. Future work may encompass identifying threshold eGFR that validates combined heart-kidney transplant in this high risk population before the progression to ESRD.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have indicated that certain patients would either benefit or have similar survival after combined HKTx compared with heart transplant alone. Those patients include heart re‐transplant, individuals with end‐stage renal disease (ESRD) on dialysis and individuals with non‐dialysis‐dependent renal impairment that is unlikely to resolve post‐heart transplant alone 10–12 . However, identifying patients who will not recover from the renal impairment after heart transplant is challenging and therefore no clear guidelines exist that recommend combined HKTx rather than heart transplant alone for any given level of kidney dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…The two early studies only described SHK outcomes as acceptable compared to HTx, but did not attempt to quantify the benefit of SHK over HTx 18,19 . The five subsequent studies quantified the benefit, with hazard ratios for post‐transplant mortality ranging from 0.36 (in heart re‐transplant patients) to 1.01 (non‐dialysis‐dependent patients), resulting in a 7%‐15% reduction in 1‐year mortality for SHK over HTx 20‐24 . These studies present two key questions: How comparable are the SHK and HTx groups? To what extent is the difference in observed survival attributable to the addition of the kidney allograft versus to other differences (measured or unmeasured) between the two groups? …”
Section: Medical Justification For Shkmentioning
confidence: 99%